Dental İşlemlerde Kullanılan Frez Tiplerinden Birkaçının Sıcaklığa Etkisinin Sonlu Elemanlar Metodu ile Modellenmesi - Sezek, Sinan (Fırat University, 2016)
Dental diş ve kemik kesme operasyonlarında yaşayan dokuların deforme olmaması çok önemlidir. Yaşayan dokular hastanın operasyon sonrası iyileşmesini hızlandıracağı gibi aksi durumda iyileşmeyi engelleyebilir. Dental ve kemik delme, kesme gibi operasyonlarda dokunun canlı kalmasını sağlamak için operasyon sıcaklığı tespit edilmeli ve bu sıcaklıklarda nekroz sıcaklığı derecesine çıkılıp çıkılmadığı kontrol edilmelidir. Çalışmada dental operasyonlarda kullanılan frezlerin operasyon esnasında ortaya çıkardığı sıcaklık dağılımlarının tespiti için yapılmıştır. 1,5 ve 2,2 bar basınçta yapılan dental operasyon sırasında frezin temas ettiği alanlardaki sıcaklık değişimleri tespit edilmiş ve bu frezler arasındaki fark gösterilmiştir. Bu çalışmada laboratuvar sonuçları ve SEM modeli ile karşılaştırmalar yaparak meydana gelen sıcaklık dağılımları belirlenmiştir. Frez tipine göre çıkılan sıcaklıkların nekroz sıcaklığı bölgesinde kaldığı ancak aeratör basıncının yüksek olduğu durumlarda nekroz bölgesinin üst sınırına yaklaştığı görülmüştür.

It is essential not to deform living tissues during dental surgeries involving teeth and dentine cutting operations. Presence of living tissues would accelerate post-operative recovery of the patient. On the contrary, deformation in living tissues is quite likely to impede recovery. During dental surgeries involving operations such as bone drilling and cutting, operation temperature should be determined to ensure that the living tissues remain mostly undeformed and checks should be made to identify whether necrosis temperature degree has been reached at those temperatures. Our study has been conducted to determine temperature degrees generated during the operation due to use of dental drills in dental surgeries. Changes in temperature occurring at drill contact areas during dental operations carried out at a pressure of 1.5 and 2.2 bars have been identified and respective differences have been shown accordingly. In this study, comparisons with lab results and FEM model have been made to determine temperature distribution patterns. It has been observed that temperatures reached according to the type of dental drill used have remained within the boundaries of necrotic temperature area but approached the upper limit of necrotic area in cases where the pressure of aerator was high.
Modelling Effects of Some Dental Burs Types on Temperature by Fem